A novel strontium-based MOF: synthesis, characterization, and promising application in removal of 152+154Eu from active waste. Issue 21 (29th April 2022) - Hamouda, Mohamed A.; Sheta, Sheta M.; Sheha, Reda R.; Kandil, A. T.; Ali, Omnia I.; El-Sheikh, Said M.
Abstract : Removal of hazardous radioactive materials such as 152+154 Eu from active waste using the batch approach based on a promising novel strontium metal–organic framework (MTSr-MOF). Abstract : Removal of hazardous radioactive materials such as 152+154 Eu from active waste using the batch approach has attracted attention nowadays. In this work, a novel melamine–terephthalic strontium metal–organic framework (MTSr-MOF) was prepared via a hydrothermal method. The MTSr-MOF was characterized by various analytical techniques such as FT-IR, 1 H/ 13 C-NMR, mass spectroscopy, XPS, XRD, TGA, BET, FE-SEM/EDX, TEM, and UV. The obtained data revealed that MTSr-MOF exhibited brick-like building blocks that were bridged together by the linkers, and each block had a thickness of ∼120 nm. The BET surface area was 74.04 m 2 g −1 . MTSr-MOF was used for the removal of 152+154 Eu radionuclides from active waste. Further functionalization using various modifiers, including oxalic acid, EDTA, sulfuric acid, and sodium hydroxide was carried out to improve the sorption efficiency of MTSr-MOF towards 152+154 Eu radionuclides. Among them, MTSr-MOF modified with oxalic acid (MTSr-OX-MOF) demonstrated a superior removal efficiency toward 152+154 Eu radionuclides when compared to MTSr-MOF or other published reports, with a removal efficiency of more than 96%. The higher sorption efficiency of the MTSr-OX-MOF indicates that it could be a promising candidate for the removal of 152+154 Eu radionuclides from radioactive waste